A New 1-ϕ, Seventeen Level Inverter Topology With Less Number of Power Devices for Renewable Energy Application - Chamarthi, Phani Kumar; Agarwal, Vivek; Al-Durra, Ahmed (Frontiers in Energy Research, 2020)
In this paper, a new seventeen level inverter topology is proposed for single-phase grid-connected renewable energy applications. The proposed inverter topology can provide seventeen levels in the output voltage while using a lesser number of power devices. This proposed inverter topology comprises nine power switches, five power diodes and two sets of DC sources (two 3V and two V) which are in the ratio of 1:3. By properly arranging the input DC sources, power switches, and power diodes through different possible combinations the seventeen voltage levels are generated. The main advantage of this seventeen level inverter is that a maximum of six power devices conducts in any mode. Thus conduction losses are lesser compared to existing seventeen level inverter topologies which results in a highly efficient system. Further, the detailed comparison of proposed inverter topology with the existing multilevel inverter (MLI) topologies shows that the number of required power devices count is considerably lower. The possible extension of the proposed inverter topology for the three-phase application is also discussed. Further, a level-shifted based pulse modulation strategy is proposed to control the output of the proposed inverter. To verify the operation, the proposed inverter topology is simulated in MATLAB/Simulink for a 500W grid-connected system. All the major results are included in the paper. The experiments are performed to validate the proposed inverter topology for a 500W grid-connected system and all the key results are included in the paper.